The Impact Of Using Technology And Innovation In Law Enforcement In The Era Of Digitalization - Prayatno, Cecep; Tohari, Mohamad; Susilowati, Tri (Al-Makki Publisher, 2024)
In an era of rapid digitalization, technology and innovation have fundamentally transformed the landscape of law enforcement. This article examines the profound impact of information technology on various aspects of law enforcement in the digital age. It offers a comprehensive review of how technology has reshaped evidence collection, surveillance, rule enforcement, and dispute resolution processes. Additionally, the article discusses the challenges and opportunities the legal system faces in adapting to these technological advancements. Utilizing a literature review methodology, the research analyzes case studies and conceptual frameworks to provide a deeper understanding of how technology enhances the effectiveness and efficiency of law enforcement while considering its broader implications for justice and human rights. Furthermore, this study lays the groundwork for future research, encouraging further empirical exploration of these critical issues. This research examines the impact of technology on the accessibility of justice, highlighting both its potential to democratize legal services and the challenges it poses, such as privacy concerns and security risks. By exploring these dynamics, the study lays the groundwork for future research on the evolving role of technology in law enforcement and legal systems.